2014
DOI: 10.5539/ijps.v6n3p53
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Participation of Parents in the Education of Mexican High School Students: Relation with Gender and Level of Studies

Abstract: The purposes of the study consisted of describing the profiles of subgroups of the parents of high school students based on their participation in the education of their children and establish the relation of these profiles with the gender and level of studies of fathers and mothers. By using a simple random sampling, 374 parents of high school students were selected to participate; of these, 173 (46.2%) questionnaires were answered by fathers and 201 (53.7%) by mothers. By using a K-means cluster analysis, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Machismo and marianismo, for fathers and mothers respectively, differentiate social roles in Latin culture by gender and represent a significant part of norms underlying many of the mechanisms promoting traditional gender roles and ideologies (Falicov, 2010;Mendez-Luck et al, 2016). Research on Latino parenting remains inconclusive, with some research showing that although gender ideologies in Latino families persist over generations, these ideologies are not predictive of father involvement (Bronstein, 1984), even when fathers receive more education, although more educated mothers are more involved (Cuervo et al, 2014). Other research, however, has shown that more equitable gender ideologies in Latino families and higher levels of paternal education will increase the likelihood of father involvement (Kato-Wallace et al, 2014;Taylor & Behnke, 2005).…”
Section: Parental Involvement Of Immigrants From Latin Americamentioning
confidence: 99%
“…Machismo and marianismo, for fathers and mothers respectively, differentiate social roles in Latin culture by gender and represent a significant part of norms underlying many of the mechanisms promoting traditional gender roles and ideologies (Falicov, 2010;Mendez-Luck et al, 2016). Research on Latino parenting remains inconclusive, with some research showing that although gender ideologies in Latino families persist over generations, these ideologies are not predictive of father involvement (Bronstein, 1984), even when fathers receive more education, although more educated mothers are more involved (Cuervo et al, 2014). Other research, however, has shown that more equitable gender ideologies in Latino families and higher levels of paternal education will increase the likelihood of father involvement (Kato-Wallace et al, 2014;Taylor & Behnke, 2005).…”
Section: Parental Involvement Of Immigrants From Latin Americamentioning
confidence: 99%